2020
DOI: 10.3354/meps13299
|View full text |Cite
|
Sign up to set email alerts
|

Population comparison of right whale body condition reveals poor state of the North Atlantic right whale

Abstract: The North Atlantic right whale Eubalaena glacialis (NARW), currently numbering <410 individuals, is on a trajectory to extinction. Although direct mortality from ship strikes and fishing gear entanglements remain the major threats to the population, reproductive failure, resulting from poor body condition and sublethal chronic entanglement stress, is believed to play a crucial role in the population decline. Using photogrammetry from unmanned aerial vehicles, we conducted the largest population assessment o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
119
2
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 91 publications
(128 citation statements)
references
References 74 publications
(72 reference statements)
6
119
2
1
Order By: Relevance
“…These values are similar to our mean body condition results (1.15 ± 1.49) Overall, North Atlantic right whale health parameter scores were higher (reflecting poorer condition) during calving years and for presumed dead whales (Pettis et al 2004), underscoring the fact that visual health assessment methods are useful for measuring individual fitness when individuals are assessed over multiple seasons. A similar pattern has been seen using overhead images (Christiansen et al 2020), with juvenile, adult and lactating female SRWs across 3 calving grounds found to be in better body condition than North Atlantic right whales at equivalent stages.…”
Section: Origin and Body Condition Of South Georgia Srwssupporting
confidence: 74%
“…These values are similar to our mean body condition results (1.15 ± 1.49) Overall, North Atlantic right whale health parameter scores were higher (reflecting poorer condition) during calving years and for presumed dead whales (Pettis et al 2004), underscoring the fact that visual health assessment methods are useful for measuring individual fitness when individuals are assessed over multiple seasons. A similar pattern has been seen using overhead images (Christiansen et al 2020), with juvenile, adult and lactating female SRWs across 3 calving grounds found to be in better body condition than North Atlantic right whales at equivalent stages.…”
Section: Origin and Body Condition Of South Georgia Srwssupporting
confidence: 74%
“…4,5 Decreasing body size may therefore be associated with smaller calves and lower calf survivorship, or potentially delayed first calving and lower reproductive success in females. NARW exhibit generally poor body condition compared to other populations of right whales, 17,18 which could contribute to synergistic negative effects where females in poor condition produce smaller calves that ultimately reach smaller maximum sizes, further contributing to reduced calf growth and declining calf condition. In addition, our results suggest that sub-lethal entanglements constrain overall body size in NARW, which may in turn make them less resilient to future entanglements by reducing their absolute energetic reserves and increasing the probability of a lethal entanglement.…”
Section: Reportmentioning
confidence: 99%
“…If the issues with identifying reference points in this area can be resolved (e.g., software program modifications), the low variation achieved for replicate TBL measurements (1%–2%) suggests that small 1–2 cm changes in width would be detectable and thus useful for assessing body condition of dwarf minke whales and other cetaceans. Alternatively, further processing of suitable frames through an additional program that automatically calculates width at select intervals along the body (e.g., Christiansen et al, 2020; Torres and Bierlich, 2020) may provide a solution to the issue of manually identifying reference points inherent to the image processing software used herein.…”
Section: Discussionmentioning
confidence: 99%
“…Determining growth rates and size at sexual maturity can provide insights into population and social structures (Shane, Wells, & Würsig, 1986), reproduction, and other life history characteristics (Blueweiss et al, 1978). Morphometry can also be used to assess body condition/fitness and provide insights into sublethal (i.e., energetic) threatening processes such as declining food availability (Bradford et al, 2012; Christiansen, Dujon, Sprogis, Arnould, & Bejder, 2016; Christiansen et al, 2020; Lockyer, 1986; Miller, Best, Perryman, Baumgartner, & Moore, 2012). Concerns for cetacean populations are increasing due to a number of threats, including anthropogenic disturbance (Evans, 1996; National Research Council, 2005; Pirotta, 2018) and climate change, in particular the effects of changes in food availability for baleen whales in high latitude feeding areas (Fabry, McClintock, Mathis, & Grebmeier, 2017; Tulloch et al, 2019).…”
Section: Introductionmentioning
confidence: 99%